A plant RNA virus inhibits NPR1 sumoylation and subverts NPR1-mediated plant immunity - Jiahui Liu; Xiaoyun Wu; Yue Fang; Ye Liu; Esther Oreofe Bello; Yong Li; Ruyi Xiong; Yinzi Li; Zheng Qing Fu; Aiming Wang; Xiaofei Cheng (Nature Communications, 2023)
Abstract NONEXPRESSER OF PATHOGENESIS-RELATED GENES 1 (NPR1) is the master regulator of salicylic acid-mediated basal and systemic acquired resistance in plants. Here, we report that NPR1 plays a pivotal role in restricting compatible infection by turnip mosaic virus, a member of the largest plant RNA virus genus Potyvirus, and that such resistance is counteracted by NUCLEAR INCLUSION B (NIb), the viral RNA-dependent RNA polymerase. We demonstrate that NIb binds to the SUMO-interacting motif 3 (SIM3) of NPR1 to prevent SUMO3 interaction and sumoylation, while sumoylation of NIb by SUMO3 is not essential but can intensify the NIb–NPR1 interaction. We discover that the interaction also impedes the phosphorylation of NPR1 at Ser11/Ser15. Moreover, we show that targeting NPR1 SIM3 is a conserved ability of NIb from diverse potyviruses. These data reveal a molecular “arms race” by which potyviruses deploy NIb to suppress NPR1-mediated resistance through disrupting NPR1 sumoylation.